The role of flag leaf blade and awns on yield and its components of some bread wheat varieties at two locations of sulaimani region - Towfiq, Sherwan Ismail; Noori, Shang Haseeb Abdulqader (Sulaimani Journal for Pure and Applied Sciences, 2016)
This investigation was conducted during the growing season of 2009-2010, at two different locations (Qlyasan Agriculture Research Station, College of Agricultural sciences- University of Sulaimani, and farm land in Dukan), using split-split plots design in RCBD with four riplications. Four common wheat varieties of different origins (Araz, Tamuz, Rabea'a, and Cham-4) were used grown and implemented in the main plots. Four seeding rates of (120, 160, 200, and 240) kg/ ha implemented in the sub-plots as the second factor, while four leaf and awn removal treatments as the third factor were implemented in the sub-sub plots that were (control, flag leaf blade removal, awns removal, and flag leaf blade + awns removal). Grain yield with some of its components were measured such as number of spikes/ m 2 , spike weight/ m 2 , spike length, number of spikelets/ spike, number of grain/ spike, grain weight/ spike, 1000- grain weight, and grain yield). Data on biological yield and harvest index were also recorded. The results of grain yield and its components with biological yield, and harvest index can be summarized as the average of both locations as follows: the effect of varieties on these characteristics was highly significant, Araz variety showed maximum values for the characteristics: number of spikes/ m 2 , spike weight/ m 2 , average spike length, and harvest index. Tamuz variety exhibited maximum number of spikelets/ spike, and grain number/ spike, while Rabea'a variety showed maximum values for the characteristics: grains weight/ spike, 1000- grains weight, grain yield, and biological yield. However, Tamuz variety produced minimum values for the characteristics; spike weight/ m 2 , grain weight/ spike, 1000- grains weight, grain yield, biological yield, and harvest index. The effect of seeding rates on yield characteristics and its components as the average of both locations was highly significant on number of spike / m 2 , spike weight/ m 2 , grain yield, and biological yield only, using the seed rate of 240 kg/ ha exhibited maximum values for these characteristics, while 120 kg/ ha seeding rate showed minimum values in number of spikes / m 2 , grain yield, and biological yield. Regarding the effect of removal treatments on yield characteristics, and its components as the average of both locations, the characteristics, number of spikes/ m 2 , spike weight/ m 2 , grain weight/ spike, 1000- grains weight, grain yield, and biological yield highly significant responded to these effects. While the characteristics number of spikelets/ spike, significantly responded, and the characteristics average spike length, number of grains/ spike, and harvest index showed no significant respons. The control treatments produced maximum values of yield and its components, while removing both flag leaf blade + awn showed minimum values in spike weight/ m 2 , grains weight/ spike, 1000- grains weight, and grain yield.
Keywords: Wheat varieties; Seeding rates; and removal treatments